The Influence of Interest and Perceived Relevance on Students’ Decision to Continue Their Studies - Margriet Puspa Dewi; Nur Azizah Azma (Journal La Sociale, 2026)
his study aims to determine and analyze the influence of interest and perceived relevance on the decision to continue studies at hospitality higher education institutions among twelfth-grade students majoring in hospitality at SMK Negeri 6 Palembang and SMK Madyatama Palembang. This research is motivated by the phenomenon of relatively low interest among some vocational high school students to continue their education to higher levels, despite the growing hospitality industry demanding professional workers. This study employed a quantitative approach with survey methods. The population consisted of 108 twelfth-grade students from both schools, and the saturated sampling technique was used, making the entire population the research sample. Data were collected through questionnaires and analyzed using multiple linear regression analysis with SPSS version 27. The results showed that (1) interest has a positive and significant influence on the decision to continue studies at hospitality higher education institutions; (2) perceived relevance has a positive and significant influence on the decision to continue studies at hospitality higher education institutions; and (3) simultaneously, interest and perceived relevance have a significant influence on the decision to continue studies at hospitality higher education institutions, with an adjusted R² value of 0.466, indicating that 46.6% of the variation in students' decisions can be explained by these two variables. These findings imply that the higher the students' interest and the more positive their perception of the relevance of hospitality higher education to the world of work, the greater their tendency to continue their studies in higher education.